A clinical pilot study for personalized risk-based breast cancer screening utilizing a polygenic risk score - Tone Hovda; Siim Sober; Peeter Padrik; Krista Kruuv-Kao; Eli Marie Grindedal; Tone Bøe Aaman Vamre; Eline Eikeland; Solveig Hofvind; Kristine Kleivi Sahlberg (PLoS ONE, 2026)
Background Population-based mammographic screening is primarily age-based. However, breast cancer risk is multifactorial, and women may benefit from personalized risk-based screening. This pilot study aimed to explore the use of polygenic risk score (PRS) as a tool for risk stratification in personalized screening. Methods We included 80 women aged 40–49 years referred for clinical mammography. Exclusion criteria were prior breast cancer or premalignant breast disease, and previous genetic testing. After DNA collection, PRS was calculated from 2805 Single Nucleotide Polymorphisms (SNPs). Screening recommendations were based on each participant’s relative 10-year breast cancer risk estimated from PRS and compared with the 10-year risk of an average woman of the same age. Women with a self-reported family history of cancer meeting standard criteria were referred for gene panel testing for pathogenic variants in high-risk genes. A follow up questionnaire regarding participants’ experiences was distributed 6–9 months after PRS testing. Results Mean age was 45.2 years (SD 2.8). Mean relative 10-year breast cancer risk was 1.18 (SD 0.57). Based on PRS, 40 participants were recommended standard biennial screening 50–69 years, while 40 were advised to begin biennial screening before age 50. Among these, 7 were recommended annual mammography from when their 10-year risk reached twice that of an average 50-year-old. Twenty-one women underwent gene panel testing; no pathogenic variants in breast cancer genes were identified. Five women were advised annual mammography from 40–60 years due to family history of breast cancer, regardless of PRS. Most respondents viewed breast cancer risk assessment positively and did not report increased anxiety after testing. Conclusions In this pilot cohort, PRS-based risk stratification led to earlier or more intensive screening recommendations in half of the participants, while family history also influenced management.